Efficacy and safety of decamethoxin in complex treatment of patients with group III viral-bacterial community-acquired pneumonia - O.L. Bororova (Civic Union "Communicable Diseases Intensive Care Association", 2021)
BACKGROUND. There are many unsolved medical problems and, of course, pneumonia is one of them. Communityacquired pneumonia (CAP) is a multifactorial disease, but the role of viruses as causative agents is constantly growing. Specific antiviral therapy for CAP is limited. Therefore, the search for drugs with virucidal activity remains relevant. An antimicrobial agent with a broad spectrum of action - decamethoxin - is successfully used today for treatment of patients with infectious exacerbations of bronchial asthma and chronic bronchitis. At the same time efficacy of decamethoxin in CAP patients was not studied. OBJECTIVE. To evaluate the effectiveness and safety of the inhaled antimicrobial drug decamethoxin in the complex treatment of patients with group III viral-bacterial CAP. MATERIALS AND METHODS. There was enrolled 62 patients with group III viral-bacterial CAP. All patients received the same sequential antibiotic therapy: protected aminopenicillin with macrolide or III generation cephalosporin with macrolide. Patients of the main group were prescribed inhalations through a nebulizer of the antiseptic drug decamethoxin in addition to antibacterial therapy from the first day of treatment for 5-7 days. RESULTS AND DISCUSSION. No adverse events were detected in any of the patients during treatment. In all cases, recovery was diagnosed. At the same time, the term of achieving positive results in the main group was 12.2±0.7 days, and in the control - 17.2±0.7 (р <0,05). The average duration of antibiotic use was different in main and control groups: respectively 9.4±0.4 and 10.7±0.4 days (р <0,05). There were no infectious complications in the patients of the main group, while 24 (72 %) patients of the control group were diagnosed with acute rhinopharyngitis (47.0 % of cases), lateral pharyngitis (13 %) and sinusitis (9 %), other complications (otitis, infectious exudative pericarditis). In 22 (66 %) cases there was one complication and in 2 (6 %) cases there were two complications. CONCLUSIONS. For patients with group III viral-bacterial CAP additional inclusion in the empirical sequential antibiotic therapy of inhaled decamethoxin can significantly reduce the frequency of infectious complications, duration of antibiotic therapy, as well as the duration of positive treatment results.